تحليل جغرافي لتلوث الهواء في مدينة النجف الاشرف - الربيعي، داود جاسم دعيج; التغلبي، زينب عبدالرزاق عبدالحسين; البغدادي، عبدالصاحب ناجي رشيد (جامعة الكوفة - كلية الآداب, 2015)
The study seeks to reveal the reality of the problem of air pollution external and internal in the holy city of Najaf and to identify the most important sources and factors affecting the different dimensions temporal and spatial The study revealed the following: - 1 - The amount of dust falling in the holy city of Najaf was great especially in the summer and reached (122.7) g \ m 2, and the spatially recorded Yarmouk district highest amount dust hit (139.95) g \ m 2 because of dust storms and neighboring city of Western Sahara, and poor soil and lack of vegetation, which reduces the severity of dust storms. 2 - The results indicate high concentrations of minutes outstanding, record summer highest concentrations in most sampling sites and reached (116.7) Micro g \ m 3, the spatially has recorded the highest rate of concentration minutes outstanding was in the neighborhood of teachers and reached (199.98) Micro g \ m 3 due to the movement of transport and proximity to the neighborhoods of Aden and industrial artisans. 3 - The study revealed high concentrations of gases in the air outside. Which reported higher concentrations in the summer, there are some gases have exceeded environmental determinants in the summer, including the gas carbon monoxide and reached (31.9), while sulfur dioxide (0.6), while the gases that were within the environmental determinants in chapter Summer is hydrogen sulfide gas was (0.3), and methane (0.06) and ammonia (0.4), and oxygen gas (19.3%). At the level of spatial find the highest concentration of gas carbon monoxide log in Ghadir district (55.5) due to increased car exhaust and smoke generators private and public. The highest concentration of sulfur dioxide in the Yarmouk district (0.75), and the highest concentration of hydrogen sulfide gas in the neighborhood of Arabism (0.45) , and the highest concentration of methane in the neighborhoods Alassane Bourne and Jihad (0.1), and the highest concentration of ammonia gas in Hawraa Zeinab (0.35) , and less oxygen Tercazelghaz in neighborhoods justice and teachers (19.9%).
يسعى هذا البحث إلى الكشف عن واقع مشكلة تلوث الهواء في مدينة النجف الاشرف والتعرف على اهم المصادر والعوامل المؤثرة في اختلاف أبعادها الزمانية والمكانية . وتبين:- 1- إن كمية الغبار المتساقط في مدينة النجف الأشرف كانت كبيرة خاصة في فصل الصيف وبلغت(122.7) غرام \ م2 ، أما مكانيا فقد سجل حي اليرموك أعلى كمية غبار متساقط وبلغ (139.95)غرام \ م2بسبب العواصف الغبارية ومجاورة المدينة للصحراء الغربية, وفقر التربة وقلة الغطاء النباتي الذي يقلل من حدة العواصف الغبارية . 2- تشير نتائج البحث إلى ارتفاع تراكيز الدقائق العالقة ، وسجل فصل الصيف أعلى تراكيز في اغلب مواقع العينات وبلغ (116.7) مايكرو غرام \ م3 ،أما مكانيا فقد سجل أعلى معدل لتركيز الدقائق العالقة كان في حي المعلمين وبلغ (199.98) مايكرو غرام \ م3 بسبب حركة وسائط النقل وقربه من حي عدن وحي الحرفيين الصناعي . 3- كشفت البحث ارتفاع تراكيز الغازات في هواء مدينة النجف. حيث سجلت تراكيز أعلى في فصل الصيف .هناك بعض الغازات قد تجاوزت المحددات البيئية في فصل الصيف ومنها غاز أول اوكسيد الكاربون وبلغ (31.9)جزء بالمليون ,أما غاز ثاني أوكسيد الكبريت (0.6)جزء بالمليون , أما الغازات التي كانت ضمن المحددات البيئية في فصل الصيف هي غاز كبريتيد الهيدروجين بلغ (0.3)جزء بالمليون , وغاز الميثان (0.06)جزء بالمليون وغاز الامونيا (0.4)جزء بالمليون, وغاز الأكسجين(19.3%).أما على مستوى المكاني نجد أن أعلى تركيز لغاز أول اوكسيد الكاربون سجل في حي الغدير (55.5) جزء بالمليون بسبب زيادة عوادم السيارات ودخان المولدات الخاصة والعامة. وبلغ أعلى تركيز لغاز ثاني أوكسيد الكبريت في حي اليرموك (0.75)جزء بالمليون ,وأعلى تركيز لغاز كبريتيد الهيدروجين في حي العروبة (0.45)جزء بالمليون , وأعلى تركيز لغاز الميثان في الأحياء الحسن والغدير والجهاد (0.1)جزء بالمليون ,وأعلى تركيز لغاز الامونيا في حي الحوراء زينب (0.35)جزء بالمليون, واقل تركيزلغاز الأكسجين في الأحياء العدالة والمعلمين (19.9%).
Keywords: تلوث الهواء; العواصف الترابية; النجف الاشرف